Poly(3-hydroxybutyrate) synthesis by recombinant Escherichia coli arcA mutants in microaerobiosis - Nikel, Pablo Ivan (2006)
We assessed the effects of different arcA mutations on poly(3- hydroxybutyrate) (PHB) synthesis in recombinant Escherichia coli strains carrying the pha synthesis genes from Azotobacter sp. strain FA8. The arcA mutations used were an internal deletion and the arcA2 allele, a leaky mutation for some of the characteristics of the Arc phenotype which confers high respiratory capacity. PHB synthesis was not detected in the wild-type strain in shaken flask cultures under low-oxygen conditions, while ArcA mutants gave rise to polymer accumulation of up to 24% of their cell dry weight. When grown under microaerobic conditions in a bioreactor, the arcA deletion mutant reached a PHB content of 27% ± 2%. Under the same conditions, higher biomass and PHB concentrations were observed for the strain bearing the arcA2 allele, resulting in a PHB content of 35% ± 3%. This strain grew in a simple medium at a specific growth rate of 0.69 ± 0.07 h-1, whereas the deletion mutant needed several nutritional additives and snowed a specific growth rate of 0.56 ± 0.06 h-1. The results presented here suggest that arcA mutations could play a role in heterologous PHB synthesis in microaerobiosis.